Amphibian chytrid fungus in Africa – realigning hypotheses and the research paradigm. (23rd September 2019) - Doherty‐Bone, T. M.; Cunningham, A. A.; Fisher, M. C.; Garner, T. W. J.; Ghosh, P.; Gower, D. J.; Verster, R.; Weldon, C.
Abstract: The amphibian chytrid fungus Batrachochytrium dendrobatidis ( Bd ), responsible for numerous amphibian declines and extinctions, was previously thought to originate from the African continent. This was based on infected museum specimens from early 20th century South Africa, Cameroon and Uganda. Further research on archived specimens from other continents eventually revealed early 20th century records also in Brazil and Japan. Recent robust analysis of genomic diversity and phylogeny of Bd has shown origin from Asia to be more plausible. This raises the issue that the threat of Bd for African amphibians as a novel pathogen has been underestimated. There are now cases where dramatic amphibian declines in disparate mountains on the continent could be attributed to Bd, and this necessitates an urgent realigning of hypotheses and the research agenda for amphibian conservation on the continent. Notably, hotspots of amphibian host naivety include West Africa where this pathogen has so far not been detected. We discuss research gaps that amphibian conservationists might focus on, notably more genomic sequencing of the Bd CAPE (the less virulent) lineage to determine its date of emergence, and assessing the susceptibility of different amphibian species to infection, disease and decline to better prioritize conservation actions. Abstract : Recent genetic evidence suggests amphibian chytrid fungus ( Bd ) is non‐indigenous to the African continent. This paper reviews the implications of this for conservation of amphibians on the continent, Bd likely being more significant as a novel pathogen. Research gaps identified include the need for further sampling of isolates to understand the distribution of different strains, understanding the responses of various species to infection, and monitoring of prioritised amphibian populations, especially on mountains and areas where Bd has not been detected.